One-Rod Contraceptive Implant as a Postpartum Contraceptive Option - Nurdiawan, Windi (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
In an effort to increase family planning coverage, reduce high-risk pregnancies, reduce the incidence of unwanted pregnancies, and reduce maternal mortality, long-acting reversible contraceptives (LARC) in the form of IUDs and implants are routinely used as postpartum contraception. Postpartum contraception use supports the reduction of maternal and infant morbidity and mortality rates.The use of implant contraception has undergone several developments from six-rods, two-rods to one-rod. A one-rod contraceptive refers to a type of LARC implant, typically containing a progestin hormone, that is inserted under the skin of a woman’s upper arm. Included among the contraceptive techniques thought safe for immediate postpartum usage, it offers efficient, reversible contraception for several years (generally 3-5 years depending on the brand). A postpartum contraceptive helps to avoid unplanned and closely spaced pregnancies, allows a woman’s body enough time to recover from birth, therefore lowering the risk of maternal anemia and other complications, also progestin-only contraceptives and non-hormonal strategies are usually preferred for breastfeeding women as estrogen-containing methods may lower milk production.